Supporting People with Intellectual Disability Who Have Experienced Abuse: Clinical Psychologists' Perspectives. Issue 1 (5th December 2019) - O'Malley, Grace; Irwin, Lynn; Guerin, Suzanne
Abstract: While sexual and other forms of abuse constitute significant problems with people with intellectual disability (ID), there is limited evidence to guide psychologists working with this population. The research involved a qualitative, interview‐based study of six clinical psychologists' views on supporting people with ID who experienced abuse. Four topics relating to service provision were explored using thematic analysis (Braun & Clark, 2006). Five overarching themes were identified. These were (1) therapeutic adaptations and creativity, (2) invalidation and exclusion, (3) too many "catch all" approaches, (4) absence of supports, and (5) mixed attitudes in approaching abuse. In the absence of a sufficient evidence base, there is great variance in therapeutic supports offered to individuals with an abuse history. A number of issues, such as the importance of supervision, the potential for acquiescence, and the need for greater definition of the role of psychologists and staff are discussed.